studies of human interferon a B and Y activities on diffrent cell - Baghdad Science Journal (مجلة بغداد للعلوم)
Human interferon as is the case in all kinds of interferon has complex effects but all share their impact on preventing the proliferation of viruses and preventing or reducing human Alantervjørn conversion occurs if the cell is in preventing the growth of the virus when interferon Balnmstqubl connects